Implikasi Hukum Terhadap Notaris Yang Memberikan Jasa Kenotariatan Di Luar Kewenangannya - Dondy Permana Putra (Lex Renaissance, 2020)
This study examines the legal implications for notaries who provide notary services beyond their authority, in which case the notary is an extension of the state, and in the case of a notary's accountability, it is the primary issue considering the deed they make is a strong written evidence. Hence, the first problem arises is the legal implications and accountability of the notary for their position in carrying out matters beyond their authority. Second, what is the Regional Supervisory Council (MPD)'s view of notaries who carry out matters beyond their authority. The results conclude that first, if a notary has committed a violation, they will receive civil and administrative sanctions in the form of compensation, temporary dismissal from their position or disrespectful dismissal. Second, the implementation of supervision and coaching that has been carried out by the Notary Supervisory Council must prioritize communication between the Central Supervisory Council (MPP), the Provincial Supervisory Council (MPW), the Regional Supervisory Council (MPD) to the Notary themselves is very important to avoid miscommunication and to create good synergy in the implementation of supervision carried out by the Supervisory Council.